Molecular Mechanisms of Endometrial Functioning in Women with Polycystic Ovary Syndrome - A. Yu. Sambyalova (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Endocrinologic and metabolic abnormalities in polycystic ovary syndrome (PCOS) may have complex effects on the endometrium, contributing to the infertility and endometrial disorders observed in women with this  syndrome. The consequences of PCOS on endometrial homeostasis and pathophysiology have not been comprehensively understood. This review provides an overview of the molecular mechanisms of endometrial  function in women with this pathology. Analysis of the literature data found that women with PCOS have changes in the effects of estrogen and progesterone in the endometrium, violation of the spatial and temporal expression of steroid receptors. In PCOS impaired follicle maturation and consequent anovulation cause a chronic progesterone-deficient state that affects the endometrial milieu. Furthermore, even with ovulation (and thus progesterone acting on endometrium), the PCOS endometrium has several abnormalities including altered expression pattern of receptivity markers during the period of implantation and glucose transporter 4 (GLUT4) expression as well as progesterone-resistance. These pathological phenomena explain the possible mechanisms of increasing endometrial cell proliferation. An imbalance in adipose tissue worsens the increase in estrogen levels and its pathological effects. Hyperandrogenia and hyperinsulinemia lead to disruption of cellular proliferation and apoptosis, affect insulin signaling and glucose metabolism, disrupting endometrial energy homeostasis. Inflammation and oxidative stress in the endometrium are closely related, and lead to increased pathological changes in the endometrium. Inflammation can induce production of inflammatory cytokines in this syndrome and directly stimulates excess  ovarian androgen production. The potential mechanisms underlying these disorders, specifically in women with PCOS, are complex and await additional transdisciplinary research for their complete elucidation.